2016
DOI: 10.5935/abc.20160165
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Treatment Adherence and Control after Participation in the ReHOT

Abstract: BackgroundLack of adherence to pharmacological treatment is one of the main causes of low control rates in hypertension.ObjectiveTo verify treatment adherence and associated factors, as well as blood pressure (BP) control in participants of the Resistant Hypertension Optimal Treatment (ReHOT) clinical trial.MethodCross-sectional study including all 109 patients who had completed the ReHOT for at least 6 months. We excluded those participants who failed to respond to the new recruitment after three phone contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
(29 reference statements)
2
10
0
4
Order By: Relevance
“…Lack of medication intake was the main obstacle in the way of adherence for the studied patients, corroborating the results of other studies on hypertensive populations (24)(25) . The discontinuation of antihypertensive medication caused by forgetfulness or incorrect timing leads to pressure oscillations that compromise control and facilitate the occurrence of negative cardiovascular events, such as acute myocardial infarction and angina (26) .…”
Section: Discussionsupporting
confidence: 90%
“…Lack of medication intake was the main obstacle in the way of adherence for the studied patients, corroborating the results of other studies on hypertensive populations (24)(25) . The discontinuation of antihypertensive medication caused by forgetfulness or incorrect timing leads to pressure oscillations that compromise control and facilitate the occurrence of negative cardiovascular events, such as acute myocardial infarction and angina (26) .…”
Section: Discussionsupporting
confidence: 90%
“…The number of medications used may also have an impact on the degree of therapeutic adherence, 5,10 which was confirmed in this study, since the group with poor adherence used a significantly higher number of antihypertensive drugs. It is important to consider this finding when making prescriptions, as the use of tablets with drug combinations may be an effective strategy to improve adherence.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of good therapeutic adherence found in this study (83%) was similar to that found in the ReHOT study, 8 which was approximately 80%, and that found by Garg et al, 9 where it was 84%. However, other studies show lower rates of good adherence, such as 31.3% found by Jesus et al, 10 51.0% found by Bloch et al, 11 and 31.2% found by Prado-Jr , et al 12 The relatively high rate of good therapeutic adherence in this study can be explained by the fact that patients are followed up at a reference outpatient clinic for Resistant Arterial Hypertension, so more attention is possibly given to the issue of adherence.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although no studies have conducted its translation and crosscultural adaptation, considering all stages of the process, several authors evaluated its properties and did not invalidate its use for this purpose, despite its limitations, mainly its low sensitivity (16)(17) . This can be evidenced by continuous use (18) , including as a gold standard for carrying out the validation of other instruments (19) . More recently, two other adherence methods were compared and it presented good agreement with both (20) .…”
Section: Study Protocolmentioning
confidence: 99%